PENGARUH GOOD CORPORATE GOVERNANCE DAN INTELLECTUAL CAPITAL TERHADAP FINANCIAL PERFORMANCE - Pardomuan, Reinhard Marthin; Tjakrawala, F.X. Kurniawan (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
The purpose of this study is to investigate the governance of manufacturing companies which include the board of directors, audit committee, institutional ownership, and intellectual capital, listed on the Indonesia Stock Exchange (IDX) between 2016 and 2020. This is an empirical assessment of the impact of corporate governance on financial performance. Data collection was carried out on 201 samples of company data selected with the purposive sampling method. The Processing of survey data is supported by the programs SPSS Output program and Microsoft Excel 2019. The results obtained indicate that the board of directors (BOD), institutional ownership (IO), and intellectual capital (VAIC) have a significant influence on financial performance (ROA). The Audit Committee (AC) does not affect the financial performance (ROA). The conclusion of this study is that not only fovernace but also intellecetual capital management needs better governance in order for companies to improve their financial performance.